Value Stocks versus Growth Stocks: An Examination Indonesia Stock Exchange - Fikral Bima E; Chandra Wijaya (Green Publisher Indonesia, 2025)
This study aims to build a portfolio of value stocks and growth stocks and identify the existence of a value premium on the Indonesia Stock Exchange during 2019-2023. T-test and Mann-Whitney U test are needed in this study to analyze performance and determine whether there is a significant difference in the returns generated by the value portfolio and the growth portfolio. The secondary data used are LQ45 companies listed on the IDX for the 2019-2023 period. The results of the study showed that there was no significant difference in returns between the value stock portfolio and the growth stock portfolio. Thus, the existence of a value premium in companies listed in the LQ45 on the IDX during the 2019-2023 period cannot be proven.